Experimental evaluation of the impact of packet length on wireless sensor networks subject to interference - Lattanzi, Emanuele; Capellacci, Paolo; Freschi, Valerio (Computer networks (Amsterdam, Netherlands : 1999), 2020)
Wireless sensor networks are nowadays considered an enabling technology for a wide spectrum of cyber-physical systems applications. However, in order to cope with stringent dependability and energy efficiency requirements, several research challenges have to be solved. Electromagnetic interference, for instance, adversely affects wireless communication, resulting into increased packet collisions and network congestion, and also increasing the energy consumption of devices. Highlighting the complex interplay between communication under interference and parameters of sensor networks is therefore mandatory for driving design choices and improving system performance. In this work we propose an experimental study of the reliability and energy efficiency of IEEE 802.15.4 compliant sensor networks under controlled interference, as a function of the packets length. The results of an extensive set of experiments on an ample range of low-power asynchronous, medium access protocols point out the trade-off between energy consumption and robustness to interference and also provide a comparative view of the protocols, thus indicating useful guidelines in the choice and in the design of several critical components.